Does amount and kind of food brought by a Household vary by indices of wealth in Nepal. - Bihel, Erin. (Tufts University. Tisch Library., 2016)
This poster uses PoSHAN data to assess if and how wealth affects food purchases made by Nepali families. Presented at the 2014 Scientific Symposium in Kathmandu Nepal.; Nutrition School: NIL Symposium Presentations, 2014.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy